Manajemen Agribisnis Peternakan Sapi Perah Kecamatan Pujon Kabupaten Malang Jawa Timur - Soeyatno, Rahmah Farahdita (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Pujon Sub-district is one of the biggest centrals that focus in milk production in Malang Regency. To reach succeed, dairy farmers in Pujon Sub-district have to know about agribusiness management. This study aims to analyze the agribusiness of dairy cow. The data were collected on September 2012 until January 2013 in Pandesari Village, Pujon Sub-district, Malang Regency, East Java. Primary and secondary data were used in this study. Primary data was taken through the interview with the dairy farmer. Secondary data was taken from relevant institutions sources. The analysis methods used qualitative description with management approach. Management is the process used to control or to direct a situation. The result of the study is the management of dairy farm agribusiness operated by dairy farmers is still have many weaknesses. It is because the maintenance of the dairy cows doesn’t well managed, such as: cleanness of shed and dairy cows are sleazy so the dairy cows will get mastitis disease easily, milking process doesn’t used warm towel when begin to redden, delays of milk handling can cause the fat content of milk at Pandesari Village amount of 2,6 percent (bellow normal standard), so it indicates that the fat content of milk is low and the milk has more than one million colony total bacteria.